2018
DOI: 10.3390/genes9050266
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of DNA Methylation Reveals Specific Regulations on Ethylene Pathway in Tomato Fruit

Abstract: DNA methylation is an essential feature of epigenetic regulation and plays a role in various physiological and biochemical processes at CG, CHG, and CHH sites in plants. LeERF1 is an ethylene response factor (ERF) found in tomatoes which plays an important role in ethylene signal transduction. To explore the characteristics of DNA methylation in the ethylene pathway, sense-/antisense-LeERF1 transgenic tomato fruit were chosen for deep sequencing and bioinformatics parsing. The methylation type with the greates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 54 publications
1
14
0
Order By: Relevance
“…As reviewed (Kyndt et al , 2013), the ET pathway plays different spatio‐temporal roles at different stages of the nematode infection process, including activation of jasmonic‐acid‐dependent defence responses. Intriguingly, research on fruit ripening has revealed a similar link between DNA hypomethylation and ET, with, for example, active hypomethylation at the induction of tomato ripening and hypermethylation during maturation of sweet oranges (Lang et al , 2017; Yin et al , 2017; Zuo et al , 2018; Huang et al , 2019). Whether temporal patterns in DNA methylation also occur during induction or maturation of nematode feeding sites remains to be investigated.…”
Section: Discussionmentioning
confidence: 97%
“…As reviewed (Kyndt et al , 2013), the ET pathway plays different spatio‐temporal roles at different stages of the nematode infection process, including activation of jasmonic‐acid‐dependent defence responses. Intriguingly, research on fruit ripening has revealed a similar link between DNA hypomethylation and ET, with, for example, active hypomethylation at the induction of tomato ripening and hypermethylation during maturation of sweet oranges (Lang et al , 2017; Yin et al , 2017; Zuo et al , 2018; Huang et al , 2019). Whether temporal patterns in DNA methylation also occur during induction or maturation of nematode feeding sites remains to be investigated.…”
Section: Discussionmentioning
confidence: 97%
“…It is known that the ethylene biosynthesis pathway involving SAM [75][76][77] contributes to DNA methylation [78]. At low SAM concentration, the expression of genes involved in DNA repair and lipid and glucose metabolism is altered [79].…”
Section: Discussionmentioning
confidence: 99%
“…ACC may be a precursor of enzymatic and non-enzymatic copper-stimulated ethylene production [ 47 ]. Interestingly, demethylation in the CG context impact on the expression of several genes involved in the ethylene synthesis and signaling pathway [ 48 ], indicating a putative regulatory role of DNA methylation [ 49 ]. Moreover, copper also participates in a broad range of biochemical pathways that cross with DNA methylation [ 50 ].…”
Section: Introductionmentioning
confidence: 99%